2001
DOI: 10.1161/hs1201.099416
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intervention and Outcome in Elderly Patients With Subarachnoid Hemorrhage

Abstract: Background and Purpose — The elderly constitute a significant and increasing proportion of the population. The aim of this investigation was to study time trends in clinical management and outcome in elderly patients with subarachnoid hemorrhage. Methods — Two hundred eighty-one pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
2
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 34 publications
1
33
2
3
Order By: Relevance
“…We were unable to evaluate the independent impact of neurointensivists on outcomes, but prior studies suggest that their presence at high-volume hospitals may account for some of the benefit. 31,32 Although we relied heavily on estimates from a large cohort study of SAH treatment in California, 7 it is likely that our conclusions would have been the same if we had used data from other published cohort studies. The differences in in-hospital mortality between high-and low-volume hospitals have been measured variably, but each study has found a significant reduction in mortality at high-volume hospitals compatible with absolute differences greater than the 2.2% threshold we found for borderline cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to evaluate the independent impact of neurointensivists on outcomes, but prior studies suggest that their presence at high-volume hospitals may account for some of the benefit. 31,32 Although we relied heavily on estimates from a large cohort study of SAH treatment in California, 7 it is likely that our conclusions would have been the same if we had used data from other published cohort studies. The differences in in-hospital mortality between high-and low-volume hospitals have been measured variably, but each study has found a significant reduction in mortality at high-volume hospitals compatible with absolute differences greater than the 2.2% threshold we found for borderline cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…1 The risk of intervention may also be lowered by new intervention techniques 13 and by better patient management. 14 We believe that low-cost screening for small cerebral aneurysms would have a signiˆcant clinical role in the near future.…”
Section: Discussionmentioning
confidence: 96%
“…In many developed countries, SAH after of 70 years of age has been a frequent pathology. 1,2,15,16,21,23,30,32,33 Some authors believe that there is not a persistent increase of rupture risk. They argue that a maximum level is reached by the age of 70 years, and then a decrease is expected.…”
Section: Discussionmentioning
confidence: 99%
“…Procedural morbidity has also been decreasing. 14,15,[19][20][21][23][24][25] In addition, unlike open surgery, endovascular morbidity and mortality seem to be less dependent on a patient's age. 11,31,34 Our series demonstrated that endovascular coiling of elderly patients with unruptured intracranial aneurysms is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation